2021
DOI: 10.1002/ajmg.a.62492
|View full text |Cite|
|
Sign up to set email alerts
|

Heterozygous variants in ZBTB7A cause a neurodevelopmental disorder associated with symptomatic overgrowth of pharyngeal lymphoid tissue, macrocephaly, and elevated fetal hemoglobin

Abstract: By clinical whole exome sequencing, we identified 12 individuals with ages 3 to 37 years, including three individuals from the same family, with a consistent phenotype of intellectual disability (ID), macrocephaly, and overgrowth of adenoid tissue. All 12 individuals harbored a rare heterozygous variant in ZBTB7A which encodes the transcription factor Zinc finger and BTB‐domain containing protein 7A, known to play a role in lympho‐ and hematopoiesis. ID was generally mild. Fetal hemoglobin (HbF) fraction was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…BTB domains are known to be strong drivers of cotranslational assembly 59 , a process that lessens the likelihood of observing a disease mechanism other than loss of function 48 . Consistently, heterozygous variants in ZBTB7A have been linked to a neurodevelopmental phenotype and are suggested to cause loss of function 60 . While the gene has not yet been classified with a cancer role in the CGC, it is increasingly being recognised as a potential cancer driver 61 .…”
Section: Identification Of Novel Candidate Tumour Suppressors and Onc...mentioning
confidence: 82%
“…BTB domains are known to be strong drivers of cotranslational assembly 59 , a process that lessens the likelihood of observing a disease mechanism other than loss of function 48 . Consistently, heterozygous variants in ZBTB7A have been linked to a neurodevelopmental phenotype and are suggested to cause loss of function 60 . While the gene has not yet been classified with a cancer role in the CGC, it is increasingly being recognised as a potential cancer driver 61 .…”
Section: Identification Of Novel Candidate Tumour Suppressors and Onc...mentioning
confidence: 82%
“…25, 49, 50 Concomitantly, studies of rare individuals with substantially elevated HbF levels have revealed rare genetic variation at the β-globin gene locus and in other genes, including BCL11A , KLF1 , and ZBTB7A , which leads to more considerable increases in HbF levels. 6, 15, 51, 52 Here, by conducting the largest multi-ancestry GWAS of HbF levels to date we have uncovered new loci underlying variation in HbF levels, including the identification of BACH2 as a new genetically-nominated regulator of HbF. We have also defined how polygenic variation can interact with rare large-effect alterations to modify HbF levels in a population stratified across extremes of the HbF distribution.…”
Section: Discussionmentioning
confidence: 99%